Visualisation of adjuvant penetration into plant waxes by fluorescence of Nile Red. - Sherin,PS; Wong,Chap Lan M; Brooks,NJ; Rueckel,M; Kuimova,MK (J Mater Chem B, 2026)
Epicuticular wax is the outermost layer of plant leaves, whose function is to protect the leaf, including preventing uncontrolled water loss. However, the resilience of this layer may present challenges in agriculture by preventing the ingress of pesticides and herbicides. Chemical formulations used in modern agrochemistry to enhance the efficiency of pesticides and herbicides often contain softening adjuvants that are expected to facilitate the permeability of waxes to chemicals. However, the mechanism of the adjuvants' action is relatively unexplored. Here, we report that an environmentally sensitive fluorophore, Nile Red (NR), can be used to directly visualise the penetration of adjuvants inside common plant waxes, such as Carnauba and Candelilla. In particular, we utilised Fluorescence Lifetime Imaging Microscopy (FLIM), which revealed that NR's emission is quenched by wax components. However, the penetration of adjuvants of different chemical structures significantly reduced the quenching, leading to an increase in NR's fluorescence intensity and lifetime. This effect allows the direct visualisation and kinetic monitoring of penetration of agrochemicals within the semicrystalline plant waxes using conventional fluorescent microscopes and opens a new area for the application of NR.